PENGUKURAN KINERJA BANK PERKREDITAN RAKYAT DI KOTA MALANG BERDASARKAN PENDEKATAN EFISIENSI DENGAN METODE DATA ENVELOPMENT ANALYSIS (DEA) - Abd. Rahman Ali (Universitas Islam Malang, 2017)
The aim of this research is to determine the level of efficiency of BPR (conventional) in Malang city and know which BPR which always reaches the maximum score in the city of Malang during the period 2014-2016. The data which is used in this research is secondary data collected from the fourth quarter IV report of all BPRs in Malang city issued by the Financial Services Authority. The sampling technique used in this research is purposive sampling with taking 6 sample of BPR in Malang. Efficiency measurements in this research using the method of Data Envelopment Analysis (DEA) with the Costan Return Scale (CRS) assumption. Input variable used in the research are asset. Third party funds and Operational expenses. While the output variable are total credit and operating income. The results of this study show that of the 6 samples of banks studied. Banks that reached 100 percent efficiency level during the period 2014-2016 namely BPR Putera Dana, BPR Armindo Kencana, BPR Tugu Artha Malang and BPR Trikarya Waranugraha with the achievement of average efficiency level of 92.4%. While the BPR always achieve maximum efficiency score for three successive periods namely BPR Armindo Kencana and BPR Trikarya Waranugraha with average efficiency score of 100%.